Thirty critical research needs for managing an ecologically and culturally unique remote marine environment: The Kimberley region of Western Australia. (15th October 2021) - Cvitanovic, C.; Mackay, M.; Kelly, R.; Wilson, S.K.; Waples, K.; Nash, K.L.; van Putten, E.I.; Field, S.; Botterill-James, T.; Austin, B.J.; Beckley, L.E.; Boschetti, F.; et al.
Abstract: The Kimberley marine environment in Western Australia is widely recognised for its outstanding natural features, vast and remote sea and landscapes, and Indigenous cultural significance. To ensure that adequate baseline information is available to understand, monitor and manage this remote and relatively understudied region, scientific exploration was undertaken between 2012 and 2018 as part of the Kimberley Marine Research Program (KMRP). Whilst this program generated significant amounts of new knowledge about the region, important research gaps remain, that if answered, should improve the capacity of managers to conserve the region's values more effectively. Here, we apply established participatory horizon scanning methods to draw on the expertise and understanding of 24 scientists and 18 managers (12 natural resource managers and 6 healthy country managers) involved in the KMRP, and assess their most essential remaining research needs for informing management of the region. Through this process, we identify a total of 184 research questions spanning seven themes: (i) habitats, (ii) fauna, (iii) ecological processes, (iv) pressures, (v) management, (vi) oceanography, and (vii) geomorphology. Of the 184 questions that formed the basis of this study, 29% related to the theme of 'management', followed by questions relating to 'fauna' (21%) and 'pressures' (20%). Questions assigned to the theme of 'habitats' (13%), 'ecological processes' (10%), and 'oceanography' (6%) were less common, whilst questions that related to 'geomorphology' only constituted 1% of all questions provided by study participants. Subtle differences in the types of questions posed by the scientist and manager groups were also evident, with questions relating to 'ecological process' and 'oceanography' overwhelmingly provided by scientists; questions in the themes 'fauna' and 'management' were mainly provided by Healthy Country Managers; and questions posed by natural resource managers were distributed evenly among all categories. Quantitative scoring of these questions by participants against set criteria of (i) achievability, (ii) importance, and (iii) the extent to which it represented an actual knowledge gap led to the identification of 30 research questions that if answered, will help to inform the management of the Kimberley marine environment. The majority of these questions (22) were related to 'management' though there were also high priority questions on 'pressures' (12), 'habitats' (11), 'fauna' (11) and 'ecological processes' (7). These questions can be used to inform and guide research effort and future funding investment in the Kimberley region. Highlights: Horizon scanning was used to identify research gaps for the Kimberley Marine Environment. Quantitative scoring of these questions identified the 30 most critical research gaps. Key research questions relate mainly to 'management' and 'pressures'. Results can help to guide research effort and funding in the region..